Carbon Molecular Sieves with High Micropore Volume Derived from Bituminous Coal and Polyimide Composites - Li, Zhen; Lin, Qingwen; Liu, Jin (Asian Journal of Chemistry, 2012)
A series of carbon molecular sieves (CMS) were obtained by carbonizing bituminous coal and polyimide composites. The process for preparing carbon molecular sieves involve three key steps: (1) preparation of the composite of bituminous coal and polyamic acid, (2) carbonization and (3) chemical activation. The process parameters including pyrolysis temperature, the content of polyamic acid and activation condition were studied. The morphology, micropore volume and pore size distribution of carbon molecular sieves were characterized by SEM and N2 adsorption. The chemical structure of carbon molecular sieves and their precursors was confirmed by FTIR. The results showed that the carbon molecular sieves prepared at a polyimide content of 20 wt % possessed more uniform pore size distribution and higher micropore volume. Their micropore volume was 0.49 cm3/g, micropore area was 900 m2/g and average pore size was 2.31 nm.